Figuras de ficção em Reynaldo Moura : A Ronda dos anjos sensuais (1935) e O Crime do apartamento (1965) - Schreiber, Tânia Beatriz (2010)
This work has as objective to analyze the main characters and the urban space in the novels A ronda dos anjos sensuais and O crime do apartamento in the “gaucho” writer Reynaldo Moura fictional universe, to understand the main characters construction and annihilation process in the space frame in which they are: Porto Alegre city in process of modernization, from 1935 to 1965, period of thirty years between one work and the other one, therefore. By means of a theoretical survey and of the study of these representative works, the first and the last, the work presents the main characters course in the space of the city and what this one contributes to the conscience and unconscience construction of these fictional characters, as well as the writer reflection about the man, the society and the world in these periods. In order to do that, it also does an outline about the “intimista” literature in Rio Grande do Sul from the analysis of these works, to evidence the relation between “intimismo” and society, as its vigorous expression of interiority and revealment of the conflicts among the individuals and of these with the modern world – empty of values and full of arbitrarinesses. The chapters which add the structure of the work concern to the theoretical content about these elements of fiction, to understand the main characters psychical texture process and the presentation of the city- space in the two “reynaldianas” novels.